GENETIC ANALYSIS AND TRAITS ASSOCIATION IN RICE (Oryza sativa L.) UNDER SALT-STRESS CONDITIONS - P. RAGHUVEER RAO and K. SUMALINI, P. HIMA BINDU, G. SHIVA PRASAD, CH. DAMODAR RAJU, RAMAN MEENAKSHI SUNDARAM (The Journal of Research, PJTSAU, 2023)
Salinity stress is one of the main problems for the rice crop, as it reduces the production and productivity of the grain yield signifcantly. Genetic variability studies provide basic information concerning the genetic properties of the population based onwhich breeding methods could be formulated for further improvement of the crop. The estimates of heritability, coefficients ofvariability and genetic advance was computed in F1s of 24 crosses for 10 characters including yield, yield contributing traits andsalt-tolerane under salinity condition during Kharif 2021. A joint consideration of PCV, GCV, heritability broad sense and geneticadvance as percentage revealed that spikelet sterility percentage (62.01, 52.35, 71.3 and 18.14%), number of unfilled grains perpanicle (50.42, 39.23, 60.5 and 25.54%) and total number of grains per panicle (26.75, 25.25, 89.1 and 109.76%) combined highPCV, GCV, high broad sense heritability and high genetic advance. High heritability coupled with high and moderate geneticadvance was observed for all the plant traits under study except for days to 50% flowering and panicle length. Correlation studiesrevealed that seed yield per plant was positively and significantly correlated with number of productive tillers per plant and totalnumber of filled grains per panicle. However seed yield plant per plant was negatively significantly associated with sterility percentage.